[OP.LB03.09] THE ACUTE EFFECT OF THE SPECIFIC CREATINE KINASE INHIBITOR BETA- GPA IN HEALTHY MAN (ABC-TRIAL): A RANDOMIZED PLACEBO AND ACTIVE CONTROLLED FIRST-IN-HUMAN TRIAL. (September 2016) - Karamat, F.A.; Horjus, D.; Haan, Y.; Van Der Woude, L.; Schaap, M.; Oudman, I.; Van Montfrans, G.; Nieuwland, R.; Clark, J.; Sturk, A.; Brewster, L.
Abstract : Objective: There is increasing evidence that the ATP generating enzyme creatine kinase (CK) is involved in hypertension. The enzyme is central to the regeneration of ATP by using creatine phosphate and ADP, thereby forming creatine and ATP. We recently showed that beta-guanidinopropionic acid (GPA), a creatine analogue and competitive CK inhibitor, effectively and safely reduced blood pressure in the spontaneously hypertensive rat. This renders GPA to be potentially beneficial for blood pressure lowering. However, no human data are available. Therefore, according to FDA and EMEA guidelines, we assessed the tolerability of a subtherapeutic GPA dose in man. Figure. No caption available. Design and method: In this randomized, placebo and active controlled, triple blind, single center trial (randomization 1:1:1), we included healthy male volunteers, 18 to 50 years old, BMI 18.5–29.9 kg/m 2, recruited in the Netherlands. The interventions consisted of one week daily oral administration of GPA in a subtherapeutic dose of 100 mg, creatine 5 gram, or placebo. The primary outcome was the tolerability of GPA as a descriptive measure, in an intent-to-treat analysis. Results: Twenty four randomized participants received the allocated intervention (8 in each treatment arm) and 23 completed the study. One participant in the placebo arm dropped out because of an external event in his family. He experienced no side effects, including not during a re-challenge with the assigned drug. GPA was well tolerated. There were no serious or severe adverse events with GPA, creatine and placebo after 1 week of active treatment, and no significant differences in safety measures including self-reported data obtained with structured and unstructured questionnaires. No abnormalities were reported from physical examination, laboratory determined toxicity including kidney and liver parameters, or cardiovascular safety including QT interval between treatment arms (Table 1). Conclusions: To our knowledge, these are the first human data of the specific CK inhibitor and potential new blood pressure lowering agent GPA. We found no evidence of toxicity with subtherapeutic doses, and will proceed to assess safety and tolerance in a dose-escalation trial in humans. Clinical trial registration number The Netherlands National Trial Register (NTR) number 4444, registered March 9, 2014.